Executive Committee Minutes 2012-03-01 - Academic Senate:::::::::
Recommendation from Structure & Functions: ACIP representative approved. Faculty Governance Assigned Time request approved. Replacement Sabbatical and Difference In Pay Policies approved for Senate agenda.